Implementasi Model Pembelajaran Kooperatif Tipe TGT untuk Meningkatkan Hasil Belajar Matematika dengan Materi Satuan Baku dan Tidak Baku Kelas IV SDN 02 Nambangan Kidul - Atikah Atikah; Candra Dewi; Ika Karlina (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Based on the observation results, the researcher found that fourth grade students felt bored with conventional mathematics learning methods so that their learning outcomes were less than optimal. To overcome this, a study was conducted using the TGT type cooperative learning model which includes educational games and tournaments. The purpose of this study was to improve the mathematics learning outcomes of fourth grade students at SDN 02 Nambangan Kidul Madiun. This study used a classroom action research approach involving 17 students in two cycles. The results showed that the application of the TGT model with the snakes and ladders game can significantly improve the average learning outcomes of students. In the initial stage, only 4 students completed the lesson, but after cycle I with lectures, 10 students completed the lesson. In cycle II with the TGT model, the number of students who completed the lesson increased to 15 students with an average score of 84.4. Therefore, the use of the TGT type cooperative learning model with games can improve students' mathematics learning outcomes and is suitable for implementation.